Costs and benefits of audiovisual interactions. (September 2022) - Tai, Jiayue; Forrester, Jack; Sekuler, Robert
A strong temporal correlation promotes integration of concurrent sensory signals, either within a single sensory modality, or from different modalities. Although the benefits of such integration are well known, far less attention has been given to possible costs incurred when concurrent sensory signals are uncorrelated. In two experiments, subjects categorized the rate at which a visual object modulated in size, while they also tried to ignore a concurrent task-irrelevant broadband sound. Overall, the experiments showed that (i) losses in accuracy from mis matched auditory and visual rates were larger than gains from matched rates and (ii) mismatched auditory and visual rates slowed responses more than they were sped up when rates matched. Experiment One showed that audiovisual interaction varied with the difference between the visual modulation rate and the modulation rate of a concurrent auditory stimulus. Experiment Two showed that audiovisual interaction depended upon the strength of the task-irrelevant auditory modulation. Although our stimuli involved abstract, low-dimensional stimuli, not speech, the effects we observed parallel key findings on interference in multi-speaker settings.